Multiple myeloma and cardiovascular risk (a literature review) - B. B. Samura; M. O. Panasenko; S. Ya. Dotsenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Multiple myeloma is a plasma cell clonal malignancy that accounts for 10 % of hematological cancers. It predominantly affects elderly people; median age at diagnosis is 70 years. Consequently, many patients with MM have cardiovascular comorbidities or risk factors. MM can cause cardiac comorbidities such as cardiomyopathy and heart failure caused by cardiac amyloidosis and/or anemia. Heart dysfunction occuring after cytostatic drugs and monoclonal antibodies intake may act as a limiting factor in multiple myeloma treatment. Side effects of chemotherapy include hypotension, hypertension, arrhythmias, conduction disturbances, pericarditis, thromboembolic events, heart failure, death.